2015
DOI: 10.5194/amt-8-1245-2015
|View full text |Cite
|
Sign up to set email alerts
|

Accurate measurements of ozone absorption cross-sections in the Hartley band

Abstract: Abstract. Ozone plays a crucial role in tropospheric chemistry, is the third largest contributor to greenhouse radiative forcing after carbon dioxide and methane and also a toxic air pollutant affecting human health and agriculture. Long-term measurements of tropospheric ozone have been performed globally for more than 30 years with UV photometers, all relying on the absorption of ozone at the 253.65 nm line of mercury. We have re-determined this cross-section and report a value of 11.27 × 10 −18 cm 2 molecule… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
65
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(73 citation statements)
references
References 26 publications
7
65
1
Order By: Relevance
“…Most cross sections are lower than that reported by Hearn (1961). The Viallon et al (2015) cross section is the lowest of all of the reported values. This 1.8 % change in the ozone absorption cross section appears to be modest.…”
Section: Introductionmentioning
confidence: 38%
See 3 more Smart Citations
“…Most cross sections are lower than that reported by Hearn (1961). The Viallon et al (2015) cross section is the lowest of all of the reported values. This 1.8 % change in the ozone absorption cross section appears to be modest.…”
Section: Introductionmentioning
confidence: 38%
“…Recent re-measurement of the absorption cross sections by Viallon et al (2015) find a cross section of (11.27 ± 0.097) × 10 −18 cm 2 molecule −1 (mean ±2σ ) that is 1.8 % lower than the Hearn (1961) evaluation. If the Viallon et al (2015) absorption cross section is officially adopted, this will imply that the ozone observations in ambient air are systematically 1.8 % higher than previously reported. Figure 1 illustrates all available ozone absorption cross sections at 253.65 nm and their uncertainties based on a compilation by Orphal (2002).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Redefinition of the value of ozone gas absorption cross section in the UV for accurate measurements of ozone gas [90] and preservation of linearity of BearLamberts law by measuring ozone gas concentration at an alternate sampling wavelength of 279.95 nm [85,91]. Ozone gas measurement in the visible spectrum using LED as a light source at 605 nm [92] and sensitivity enhancement through light propagation at incident angle [93].…”
Section: Research Challengesmentioning
confidence: 99%